Effect of metronidazole ophthalmic solution on corneal neovascularization in a rat model - Claros-Chacaltana, Flor Diana Yokoay [UNESP] (2018)
Purpose: To evaluate the effect of metronidazole ophthalmic solutions on corneal neovascularization (CNV) in a rat model. Methods: A chemical burn was created in the right central cornea of 40 rats. Animals were randomized and distributed into four study groups (n = 10 rats per group) designated Met_0.1%, Met_0.5%, sham, and untreated groups. Chemical-burned corneas in the Met_0.1% and Met_0.5% groups received ophthalmic solutions of 0.1 and 0.5% metronidazole, respectively. Corneas in the sham group received phosphate-buffered saline (metronidazole diluent). All treated eyes received ophthalmic solution at intervals of 6 h, for up to 30 days. Untreated corneas received no treatment. CNV was evaluated postinjury using corneal photographs at different evaluation time points. The main CNV outcome measures were: burn intensity, index of CNV, and percentage of vascularized corneal area. Five rats from each group were euthanized, on days 15 and 30; the samples were collected for histological analyses. Differences with P < 0.05 were considered significant. Results: CNV was observed in the eyes from day 7 postinjury. However, the indices of CNV for the Met_0.1% and Met_0.5% groups were smaller than those for the sham and untreated groups (P < 0.05). Furthermore, corneas treated with 0.1 or 0.5% metronidazole had smaller vascularized areas compared to control corneas. On histological study, the presence of blood vessels confirmed clinical outcomes. Conclusions: Regular instillation of 0.1 or 0.5% metronidazole had a significant inhibitory effect for CNV on chemical burns induced in a rat model.